Modern Teaching Based On the Influencing Factors In EFL Classroom With Second Language Acquisition (Theoretical Framework) - Sri Mujayanah; yulis setyowati; Ari Astutik (EL2J (English Language and Literature Journal), 2024)
This paper illustrates that the impacts of different factors on second language (L2) acquisition exhibit variability. Emphasizing the significance of individual diversity in second language acquisition (SLA) is crucial. Factors such as learners' motivation, attitude, age, IQ, aptitude, learning style, and personality, among others, play a role in shaping their approaches to, and potentially their success or failure in, acquiring a second language. initiates with an examination of the factors impacting second language acquisition. Thus, motivation, attitude, age, IQ, aptitude, cognitive style, and personality are acknowledged as contributing elements in second language acquisition. Certain factors are regarded as having greater influence, while others are seen as having equal significance. It is posited that typically, any child raised under normal conditions will proficiently acquire their first language.